2011
DOI: 10.1371/journal.pntd.0001005
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Tech Analytical Method for Diethylcarbamazine Citrate in Medicated Salt

Abstract: The World Health Organization has called for an effort to eliminate Lymphatic Filariasis (LF) around the world. In regions where the disease is endemic, local production and distribution of medicated salt dosed with diethylcarbamazine (DEC) has been an effective method for eradicating LF. A partner of the Notre Dame Haiti program, Group SPES in Port-au-Prince, Haiti, produces a medicated salt called Bon Sel. Coarse salt is pre-washed and sprayed with a solution of DEC citrate and potassium iodate. Iodine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…There was no practice of salt treatment before consumption in this community, in contrast with other areas where household salt may be washed and dried in direct sunlight or over afire before consumption [ 30 ]. A study in Haiti demonstrated that 5 seconds swirling coarse salt in a bowl of water leads to 60–70% retention of the iodate, while 40–30% of the iodate lost by the washing procedure [ 31 ]. Sixty percent of iodine can be lost during cooking.…”
Section: Discussionmentioning
confidence: 99%
“…There was no practice of salt treatment before consumption in this community, in contrast with other areas where household salt may be washed and dried in direct sunlight or over afire before consumption [ 30 ]. A study in Haiti demonstrated that 5 seconds swirling coarse salt in a bowl of water leads to 60–70% retention of the iodate, while 40–30% of the iodate lost by the washing procedure [ 31 ]. Sixty percent of iodine can be lost during cooking.…”
Section: Discussionmentioning
confidence: 99%
“…An annual MDA with coverage of 60-80% for 4-5 years is considered to be effective enough to interrupt transmission in control areas in the absence of vector control (Gyapong et al, 2005). Also, new options for mass treatment of at risk population are effectively available: DEC-fortified salt for 1 year; and a combination of single annual dose of albendazole plus DEC, followed by DEC-fortified salt (Weaver et al, 2011). The ample supply and distribution of DEC-fortified salt can be administered in some countries.…”
Section: Mass Chemotherapy As Elimination Strategymentioning
confidence: 99%
“…This compound has been used as the first option drug for the treatment of filariasis, a disease endemic in tropical countries and caused by adult worms of Wuchereria bancrofti , which is transmitted by mosquitoes . Due to its good thermal stability, DEC‐cit can be added to the table salt used by patients, to guarantee a good adherence to the treatment . Da Silva et al described the existence of three phase transitions, leading to four crystal packings at 293, 235, 150, and 100 K. Additionally, they also reported the existence of two possible conformers (in a 70:30 ratio) for the 293 and 235 K crystal structures due to the existence of a disorder in one of the two ethyl branches of the DEC unit.…”
Section: Introductionmentioning
confidence: 99%